Communicating Linguistics Language, Community and Public Engagement - Price, Hazel; McIntyre, Dan (Taylor & Francis, 2023)
Increasingly, academics are called upon to demonstrate the value of linguistics and explain their research to the wider public. In support of this agenda, Communicating Linguistics: Language, Community and Public Engagement provides an overview of the wide range of public engagement activities currently being undertaken in linguistics, as well as practically focused advice aimed at helping linguists to do public engagement well. From podcasts to popular writing, from competitions to consultancy, from language creation to community projects, there are many ways in which linguists can share their research with the public. Bringing together insights from leading linguists working in academia as well as non-university professions, this unique collection: • Provides a forum for the discussion of challenges and opportunities of public engagement in linguistics in order to shape best practice. • Documents best practice through a summary of some of the many excellent public engagement projects currently taking place internationally. • Celebrates the long tradition of public engagement in linguistics, a discipline which is often misunderstood despite its direct and fundamental importance to everyday life. Breaking down long-standing divisions between universities and the wider community, this book will be of significant value to academics in linguistics but also teachers, policy makers and anyone interested in better understanding the nature and use of language in society.